Sistematik Numerik Strain-Strain Anggota Genus Pseudomonas Pendegradasi Alkilbenzen Sulfonat Liniar Berdasarkan Sifat Fenotip dan Protein Fingerprinting - Suharjono Suharjono; Langkah Sembiring; Jusup Subagja; Tri Ardyati; Lisa Lisdiana (Universitas Atma Jaya Yogyakarta, 2007)
Bacteria strains consisting of Pseudomonas sp. strain J and R isolated from river ecosystem polluted and Pseudomonas sp. strain A and B isolated from river ecosystem unpolluted by detergent were capable to degrade of LAS. The objective of this research was to determine similarity value by numerically of LAS-degrading Pseudomonas strains based on phenotype character and protein fingerprinting using three reference strains consist of Pseudomonas putida FNCC071, P. fluorescens FNCC070, and P. aeruginosa FNCC063. Phenotype characteristics examined are cellular and colony morphology, biochemical nature, capability to degrade polysaccharide, tolerance to various environmental factors and antibiotics, and ability to ferment sugar. Cellular protein fingerprinting was analyzed using SDS–PAGE discontinuous. Strains classification was determined based on Simple Matching Method similarity index by UPGMA (Unweight Pair Group Method with Average) algorithm. Based on phenotype nature, all strains have similarity value 0.61; however, based on cellular protein fingerprinting, those strains have similarity value 0.52. All strains of LAS-degraded were including in the genus of Pseudomonas.